2018
DOI: 10.1104/pp.18.00840
|View full text |Cite
|
Sign up to set email alerts
|

SENSITIVE TO SALT1, An Endoplasmic Reticulum-Localized Chaperone, Positively Regulates Salt Resistance

Abstract: ORCID IDs: 0000-0002-0717-7760 (J.W.); 0000-0003-4053-8262 (C.W.); 0000-0001-6124-4242 (K.Y.); 0000-0001-6409-6855 (J.H.); 0000-0001-5194-822X (C.Z.)Salt stress seriously affects plant growth and development. Through genetic screening, we identified and characterized an Arabidopsis (Arabidopsis thaliana) sensitive to salt1 (ses1) mutant. SES1 was ubiquitously expressed and induced by salt treatment. The salt-sensitive phenotype of ses1 was due neither to the overaccumulation of Na + nor to the suppression of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 76 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…Instead, we found that BIP3 was induced by salt stress (Fig. 4C); BIP3's involvement in the unfolding protein response caused by salinity was recently discussed (Henriquez-Valencia et al, 2015;Guan et al, 2018).…”
Section: Heat Shock Transcription Factors and Heat Shock Proteins Are Mainly Induced By Heat And Combinations Of Stresses Including Heatmentioning
confidence: 63%
“…Instead, we found that BIP3 was induced by salt stress (Fig. 4C); BIP3's involvement in the unfolding protein response caused by salinity was recently discussed (Henriquez-Valencia et al, 2015;Guan et al, 2018).…”
Section: Heat Shock Transcription Factors and Heat Shock Proteins Are Mainly Induced By Heat And Combinations Of Stresses Including Heatmentioning
confidence: 63%
“…Cell wall/membrane/envelope biogenesis in microbes may enhance drought and salt stress tolerance by regulating H + -ATPase of the plasma membrane, and these can enhance plant growth and drought tolerance as plant growth-promoting bacteria [38,39]. Some chaperones, such as heat shock proteins, are known as drought tolerance enhancers for plants [40,41]. Thus the vigorous microbial metabolism and basic biological processes in the drought-treated samples may enhance peanut stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Many scientists have paid great attention to investigate the mechanisms of plant salt-tolerance and salt-adaption using genomic and proteomic technologies (Shah et al 2018;Wu et al 2016). Arabidopsis thaliana is an ideal material to investigate the salt-responsive molecules (Guan et al 2018;Zhang et al 2018;Huang et al 2018). But previous research only provided limited information.…”
Section: Discussionmentioning
confidence: 99%